Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

CmPah1 coordinates lipid metabolism and fruiting body formation in the edible and medicinal fungus Cordyceps militaris - Bing Li; Tianhao Shen; Dapeng Bao; Yan Li; Wenjie Chen; Hongyu Chen; Youran Shao; Ting Guo; Jianing Wan; Gen Zou; Ying Wang (Food Bioscience, 2026)

Magmatic–hydrothermal mineralization processes in the Xiwukou Sn–W–Rb deposit, Jiangnan orogenic belt: Constraints from multi-mineral U–Pb geochronology - Kun-Yan Wu; Xiao-Ying Gao; Qi Hou; Xiao-Yong Yang; Qiu Wan; Xiang Qian; Fu-Jun Zhong; Gen-Tao Zhou (Mineralium Deposita, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

SAR imaging simulation of ship wake on the finite depth sea surface - Gen Luo; Zhi-Hua Xiong; Ming-Bin Zhou; Jia Zhang; Qi-Xin Wan (International Journal of Remote Sensing, 2025)

Storage and release of NO3− and I− via layered double hydroxide in carbonate electrolyte for stable lithium metal battery - Fenglin Wang; Zhicheng Zheng; Zuxin Wen; Wenqiang Fang; Chengwei Kuang; Fashen Chen; Hao Wan; Ning Zhang; Xiaohe Liu; Renzhi Ma; Gen Chen (Science Bulletin, 2025)

Short-term exposure of enrofloxacin inhibits synthesis of central estradiol through secretoneurin a/aromatase B (cyp19a1b) pathway in crucian carp - Huazhong Liu; Gen Wan; Ping Luo; Jianzhen Huang; Jiayi Wu; Zhuocheng Nie; Jiming Ruan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Intelligent transportation systems: Machine learning approaches for urban mobility in smart cities - Gen Chen; Jia wan Zhang (Sustainable Cities and Society, 2024)

Disruption of sex steroid hormones biosynthesis by short-term enrofloxacin antibiotic exposure in Carassius auratus var. Pengze - Jiming Ruan; Gen Wan; Zhen Lin; Jianzhen Huang; Xiaochen Tang; Huazhong Liu (Chemosphere, 2023)

Enrofloxacin hydrochloride toxicological effects on crucian carp reflected by serological changes and neurotoxicity - Gen Wan; Jianzhen Huang; Runping Wang; Huazhong Liu; Lili Wei; Ximei Liang; Fugui Li; Zhao Wang; Xuechun Gu; Jiming Ruan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Establishment of a novel signature to predict prognosis and immune characteristics of pancreatic cancer based on necroptosis-related long non-coding RNA - Yuanpeng Xiong; Xiaoyu Kong; Kang Fang; Gen Sun; Shuju Tu; Yongyang Wei; Yonghao Ouyang; Renhua Wan; Weidong Xiao (Molecular Biology Reports, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Toxicologic effect of short-term enrofloxacin exposure on brain of Carassius auratus var. Pengze - Zhen Lin; Gen Wan; Jiayi Wu; Huazhong Liu; Fan Zhang; Xiaochen Tang; Jiming Ruan (Science of The Total Environment, 2023)

Study on the crustal stress field of the Tengchong volcanic area using composite focal mechanism method - Shu-zhong Sheng; Yong-ge Wan; Chang-sheng Jiang; Xiao-shan Wang; Shan-shan Liang; Gen-ru Xiao; Xiao-hui Hu (Applied Geophysics, 2021)

Pomc Plays an Important Role in Sexual Size Dimorphism in Tilapia - Z. Y. Wan; V. C. L. Lin; Yue Gen Hua (Marine Biotechnology, 2021)

Mapping and Validating QTL for Fatty Acid Compositions and Growth Traits in Asian Seabass - Le Wang; Elaine Chua; Fei Sun; Zi Yi Wan; Baoqing Ye; Hongyan Pang; Yanfei Wen; Gen Hua Yue (Marine Biotechnology, 2019)

QTL Mapping for Resistance to Iridovirus in Asian Seabass Using Genotyping-by-Sequencing - Le Wang; Bin Bai; Shuqing Huang; Peng Liu; Zi Yi Wan; Baoqing Ye; Jinlu Wu; Gen Hua Yue (Marine Biotechnology, 2017)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Genome-Wide Association Study Identifies Loci Associated with Resistance to Viral Nervous Necrosis Disease in Asian Seabass - Le Wang; Peng Liu; Shuqing Huang; Baoqing Ye; Elaine Chua; Zi Yi Wan; Gen Hua Yue (Marine Biotechnology, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Genetic variability, local selection and demographic history: genomic evidence of evolving towards allopatric speciation in Asian seabass - Le Wang; Zi Yi Wan; Huan Sein Lim; Gen Hua Yue (Molecular Ecology, 2016)
Genomewide analysis of genetic divergence is critically important in understanding the genetic processes of allopatric speciation. We sequenced RAD tags of 131 Asian seabass individuals of six populations from South‐East Asia and Australia/Papua New Guinea. Using 32 433 SNP s, we examined the genetic diversity and patterns of population differentiation across all the populations. We found significant evidence of genetic heterogeneity between South‐East Asian and Australian/Papua New Guinean populations. The Australian/Papua New Guinean populations showed a rather lower level of genetic diversity. F ST and principal components analysis revealed striking divergence between South‐East Asian and Australian/Papua New Guinean populations. Interestingly, no evidence of contemporary gene flow was observed. The demographic history was further tested based on the folded joint site frequency spectrum. The scenario of ancient migration with historical population size changes was suggested to be the best fit model to explain the genetic divergence of Asian seabass between South‐East Asia and Australia/Papua New Guinea. This scenario also revealed that Australian/Papua New Guinean populations were founded by ancestors from South‐East Asia during mid‐Pleistocene and were completely isolated from the ancestral population after the last glacial retreat. We also detected footprints of local selection, which might be related to differential ecological adaptation. The ancient gene flow was examined and deemed likely insufficient to counteract the genetic differentiation caused by genetic drift. The observed genomic pattern of divergence conflicted with the ‘genomic islands’ scenario. Altogether, Asian seabass have likely been evolving towards allopatric speciation since the split from the ancestral population during mid‐Pleistocene.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Mapping QTL for Resistance Against Viral Nervous Necrosis Disease in Asian Seabass - Peng Liu; Le Wang; Zi Yi Wan; Bao Qing Ye; Shuqing Huang; Sek-Man Wong; Gen Hua Yue (Marine Biotechnology, 2016)

Role of Rho Kinase and Fasudil on Synaptic Plasticity in Multiple Sclerosis - Chan Chen; Jie-Zhong Yu; Qiong Zhang; Yong-Fei Zhao; Chun-Yun Liu; Yan-Hua Li; Wan-Fang Yang; Cun-Gen Ma; Bao-Guo Xiao (NeuroMolecular Medicine, 2015)

Genome-wide discovery of gene-related SNPs in Barramundi Lates calcarifer - Le Wang; Shu Qing Huang; Jun Hong Xia; Peng Liu; Zi Yi Wan; Gen Hua Yue (Conservation Genetics Resources, 2015)

Early channel transurethral resection of the prostate for patients with urinary retention after brachytherapy - You-yun Zhang; Zhi-gen Zhang; Yan-lan Yu; Yi-cheng Chen; Kang-xin Ni; Ming-chao Wang; Wei-ping Zhao; Faisal Rehman; Shaw P. Wan; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2014)

Elevational patterns of endogenous hormones and their relation to resprouting ability of Quercus aquifolioides plants on the eastern edge of the Tibetan Plateau - Wan-Ze Zhu; San-Gen Wang; De-Zhen Yu; Yong Jiang; Mai-He Li (Trees, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The methylation of C/EBP β gene promoter and regulated by GATA-2 protein - Wan Rui; Zhang Jin; Gen Zhe; HouYan Song (Molecular Biology Reports, 2013)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Human insulin gene expressing with Bombyx mori multiple nucleopolyhedrovirus (BmMNPV) expression system - Wan-fu Yue; Fang Zhou; Jia-biao Hu; Enoch Y. Park; Joe Hull; Yun-gen Miao (World Journal of Microbiology and Biotechnology, 2011)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)